RNA-seq transcriptional profiling of Leishmania amazonensis reveals an arginase-dependent gene expression regulation. - Juliana Ide Aoki; Sandra Marcia Muxel; Ricardo Andrade Zampieri; Maria Fernanda Laranjeira-Silva; Karl Erik Müller; Audun Helge Nerland; Lucile Maria Floeter-Winter (Public Library of Science (PLoS), 2017)
Leishmania is a protozoan parasite that alternates its life cycle between the sand-fly vector and the mammalian host. This alternation involves environmental changes and leads the parasite to dynamic modifications in morphology, metabolism, cellular signaling and regulation of gene expression to allow for a rapid adaptation to new conditions. The L-arginine pathway in L. amazonensis is important during the parasite life cycle and interferes in the establishment and maintenance of the infection in mammalian macrophages. Host arginase is an immune-regulatory enzyme that can reduce the production of nitric oxide by activated macrophages, directing the availability of L-arginine to the polyamine pathway, resulting in parasite replication. In this work, we performed transcriptional profiling to identify differentially expressed genes in L. amazonensis wild-type (La-WT) versus L. amazonensis arginase knockout (La-arg-) promastigotes and axenic amastigotes.A total of 8253 transcripts were identified in La-WT and La-arg- promastigotes and axenic amastigotes, about 60% of them codifying hypothetical proteins and 443 novel transcripts, which did not match any previously annotated genes. Our RNA-seq data revealed that 85% of genes were constitutively expressed. The comparison of transcriptome and metabolome data showed lower levels of arginase and higher levels of glutamate-5-kinase in La-WT axenic amastigotes compared to promastigotes. The absence of arginase activity in promastigotes increased the levels of pyrroline 5-carboxylate reductase, but decreased the levels of arginosuccinate synthase, pyrroline 5-carboxylate dehydrogenase, acetylornithine deacetylase and spermidine synthase transcripts levels. These observations can explain previous metabolomic data pointing to the increase of L-arginine, citrulline and L-glutamate and reduction of aspartate, proline, ornithine and putrescine. Altogether, these results indicate that arginase activity is important in Leishmania gene expression modulation during differentiation and adaptation to environmental changes. Here, we confirmed this hypothesis with the identification of differential gene expression of the enzymes involved in biosynthesis of amino acids, arginine and proline metabolism and arginine biosynthesis.All data provided information about the transcriptomic profiling and the expression levels of La-WT and La-arg- promastigotes and axenic amastigotes. These findings revealed the importance of arginase in parasite survival and differentiation, and indicated the existence of a coordinated response in the absence of arginase activity related to arginine and polyamine pathways.